Further evidence of the increased risk for malignant peripheral nerve sheath tumour from a Scottish cohort of patients with neurofibromatosis type 1. Issue 7 (27th February 2007) - McCaughan, J A; Holloway, S M; Davidson, R; Lam, W W K
Abstract : A recent study, looking at the lifetime risk of developing malignant peripheral nerve sheath tumour (MPNST) in patients with neurofibromatosis type 1 (NF1), estimated the risk to be 8–13%. Prior to this, longitudinal studies had shown that patients with NF1 had a risk of 4–5% of developing MPNST, and cross-sectional studies had found that only 1–2% of patients with NF1 had MPNST. The aim of this study was to estimate the lifetime risk of MPNST in patients with NF1 in southern Scotland, using patient records obtained from the Edinburgh and Glasgow Genetic Units and Scottish Cancer Register. In the period 1993–2002, 14 patients with NF1 were diagnosed with MPNST in a population of 3.5 million. The lifetime risk of MPNST in the Scottish patients with NF1 was calculated to be 5.9–10.3%. This provides further evidence that patients with NF1 are at greater risk of developing MPNST than was previously estimated, and emphasises the importance of educating patients about suspicious symptoms, which may need an urgent medical opinion. The mean age at diagnosis of MPNST (p<0.05) and 5-year survival (p<0.01) were significantly lower in patients with NF1 than in unaffected individuals. This may be due to patients with NF1 presenting later, because the tumour is mistaken for a neurofibroma, or due to MPNST having a more aggressive course in NF1.